Terahertz time-domain spectroscopy (THz-TDS) study of Bi2O2Se and lead halide perovskite thin films - Sng, Salmah Mei Wen (Nanyang Technological University, 2024)
Terahertz (1 terahertz = 10^12 Hz) radiation falls within the region between microwave radiation and infrared radiation in the electromagnetic spectrum. The terahertz band was under- exploited for a long time, especially in comparison with other more well-known bands of the electromagnetic spectrum like microwaves and X-rays, before the technique of time-domain spectroscopy was introduced. A powerful method for studying material properties, terahertz time-domain spectroscopy (THz-TDS) uses ultrashort pulses of THz radiation that enable us to obtain the complex optical conductivity and other optical properties of a plethora of materials — these include semiconductors, superconductors, dielectrics, and liquids — without the need for the Kramers- Kronig relation. Harnessing THz radiation holds a lot of promise in fields beyond just condensed matter physics or material studies, expanding into domains like healthcare, security, meteorology and communication. In this thesis, I will be using THz-TDS to study the carrier and phonon dynamics of two- dimensional materials, mathematically derive the transmission coefficient, and convert raw THz-TDS data to optical conductivity using MATLAB. The materials studied in this thesis include the two-dimensional semiconductor bismuth oxyselenide (Bi2O2Se) and lead halide perovskites.